Social Control: Analytical Tool or Analytical Quagmire? - Chunn, Dorothy E. (1988)
There is probably no concept which is used more widely and with less precision than that of 'social control'. Given the lack of agreement about what 'social control' is, researchers usually employ the term in one of two ways. Either they assume that its meaning is obvious and requires no clarification, or, they begin with a perfunctory acknowledgment of the definitional problems associated with the concept and proceed to use it anyway. The eclecticism of the latter approach has stimulated attempts over the years to produce a universally applicable definition of 'social control' that could be empioyed both systematically and scientifically in research (Clark and Gibbs 1965, Gibbs 1977, Janowitz 1978, Mayer 1983). While these efforts are commendable and may ultimately prove fruitful, the ongoing elusiveness of such a formulation has led us in a different direction. We have concluded that the concept of 'social control' incorporates ambiguities which severely undermine its effectiveness as an analytical tool. The argument is developed in two stages: first, by tracing the historical evolution of the concept to illustrate the problematic nature of a 'social control' model, and second, by demonstrating, through an assessment of the 'women, law and social control' literature, its inadequacy as an analytical construct